Environmental Sound Perception: Metadescription and Modeling Based on Independent Primary Studies. (10th May 2010) - Misdariis, Nicolas; Minard, Antoine; Susini, Patrick; Lemaitre, Guillaume; McAdams, Stephen; Parizet, Etienne
Abstract : The aim of the study is to transpose and extend to a set of environmental sounds the notion of sound descriptors usually used for musical sounds. Four separate primary studies dealing with interior car sounds, air-conditioning units, car horns, and closing car doors are considered collectively. The corpus formed by these initial stimuli is submitted to new experimental studies and analyses, both for revealing metacategories and for defining more precisely the limits of each of the resulting categories. In a second step, the new structure is modeled: common and specific dimensions within each category are derived from the initial results and new investigations of audio features are performed. Furthermore, an automatic classifier based on two audio descriptors and a multinomial logistic regression procedure is implemented and validated with the corpus.